2020
DOI: 10.1155/2020/6130162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in Sedative Effects between Dexmedetomidine and Midazolam in Dental Implantation: A Randomized Clinical Trial

Abstract: Dexmedetomidine refers to an α2-adrenergic receptor agonist causing potent sedative, analgesic, and minimal respiratory depression compared with alternative drugs. The present study was aimed at comparing the efficaciousness and safety of midazolam and dexmedetomidine as sedatives for dental implantation. We recruited 60 patients belonging to group I or II of the American Society of Anesthesiologists (ASA) and treated them with either midazolam or dexmedetomidine in a random manner. Patients’ duration of analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Wang et al [ 1 ] reported that, in dental implant placement, DEX reduced the intraoperative heart rate significantly more than MZ and had a lower VAS pain score 135 minutes after the start of anaesthetic administration. Furthermore, in the DEX group of Wang et al [ 1 ], the time from the start of anaesthetic administration until the use of analgesics was approximately 4 hours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al [ 1 ] reported that, in dental implant placement, DEX reduced the intraoperative heart rate significantly more than MZ and had a lower VAS pain score 135 minutes after the start of anaesthetic administration. Furthermore, in the DEX group of Wang et al [ 1 ], the time from the start of anaesthetic administration until the use of analgesics was approximately 4 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 1 ] reported that, in dental implant placement, DEX reduced the intraoperative heart rate significantly more than MZ and had a lower VAS pain score 135 minutes after the start of anaesthetic administration. Furthermore, in the DEX group of Wang et al [ 1 ], the time from the start of anaesthetic administration until the use of analgesics was approximately 4 hours. In the current study, flurbiprofen axetil or acetaminophen was used at the end of surgery, and the time from the start of anaesthetic administration to the use of analgesics (as in Wang et al [ 1 ]) was approximately 6 hours in both the DM and DMF groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e addition of magnesium, clonidine, ketamine, dexamethasone, opioids, and other analgesics and local anesthetics can enhance and prolong the analgesic effect provided by PVB [8,9]. Dexmedetomidine (DEX) is a novel alpha-2 adrenergic receptor agonist with dose-dependent sedative, anxiolytic, and analgesic effects and has an advantage of minimum respiratory depression compared with alternative drugs [10]. It is well known that α-2 receptor agonists, due to their own sympathetic properties, provide stable hemodynamics during surgery and reduce the amount of narcotic analgesics.…”
Section: Introductionmentioning
confidence: 99%